Damage-Induced Calcium Signaling and Reactive Oxygen Species Mediate Macrophage Activation in Zebrafish - Sipka, Tamara; Peroceschi, Romain; Hassan-Abdi, Rahma; Groß, Martin; Ellett, Felix; Begon-Pescia, Christina; Gonzalez, Catherine; Lutfalla, Georges; Nguyen-Chi, Mai (Frontiers in Immunology, 2021)
Immediately after a wound, macrophages are activated and change their phenotypes in reaction to danger signals released from the damaged tissues. The cues that contribute to macrophage activation after wounding in vivo are still poorly understood. Calcium signalling and Reactive Oxygen Species (ROS), mainly hydrogen peroxide, are conserved early wound signals that emanate from the wound and guide neutrophils within tissues up to the wound. However, the role of these signals in the recruitment and the activation of macrophages is elusive. Here we used the transparent zebrafish larva as a tractable vertebrate system to decipher the signalling cascade necessary for macrophage recruitment and activation after the injury of the caudal fin fold. By using transgenic reporter lines to track pro-inflammatory activated macrophages combined with high-resolutive microscopy, we tested the role of Ca²⁺ and ROS signalling in macrophage activation. By inhibiting intracellular Ca²⁺ released from the ER stores, we showed that macrophage recruitment and activation towards pro-inflammatory phenotypes are impaired. By contrast, ROS are only necessary for macrophage activation independently on calcium. Using genetic depletion of neutrophils, we showed that neutrophils are not essential for macrophage recruitment and activation. Finally, we identified Src family kinases, Lyn and Yrk and NF-κB as key regulators of macrophage activation in vivo, with Lyn and ROS presumably acting in the same signalling pathway. This study describes a molecular mechanism by which early wound signals drive macrophage polarization and suggests unique therapeutic targets to control macrophage activity during diseases.